Hypnosis and superficial cervical anesthesia for total thyroidectomy in a high-risk patient – A case report. (2020) - Makovac, P.; Potié, A.; Roukain, A.; Pucci, L.; Rutz, T.; Kopp, P.A.; Matter, M.
Highlights: Total thyroidectomy can be challenging in high-risk patients. Local superficial anesthesia combined with a hypnosis-analgesia technique instead of intravenous sedation. Because of difficulties controlling the thyrotoxic state. Given the multiple cardiac and large vessel malformations, a possible variant of the inferior laryngeal nerve was expected. Locoregional deep cervical anesthesia can be associated with breathing problems when performed bilaterally. Abstract: Introduction: Total thyroidectomy can be challenging in high-risk patients. Local cervical anesthesia with sedation is an alternative to general anesthesia. Case presentation: A 33-year old male patient with cyanotic congenital heart disease due to unrepaired tricuspid atresia type Ic and associated pulmonary arterial hypertension presented with tachycardic atrial fibrillation and amiodarone-induced thyrotoxicosis resulting in recurrent hemodynamic instability. Because of difficulties controlling the thyrotoxic state, the indication for total thyroidectomy was established. Total thyroidectomy was subsequently performed using local anesthesia combined using a hypnosis-analgesia technique instead of intravenous sedation. The intervention and the post-operative course were uneventful. Discussion: A well-established therapist-patient relationship is crucial for a successful induction of hypnosis. Patient motivation and expectations are equally important for a successful implementation of this approach. Conclusion: We conclude that hypnosis combined with local anesthesia provides an effective alternative in selected patients with very high anesthesiological risk.